2003
DOI: 10.1021/ma0301496
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Composition Distribution on Microphase-Separated Structure from Diblock Copolymers

Abstract: Microphase-separated structures of diblock copolymers with narrow molecular weight distributions but with various composition distributions were investigated. Monodisperse nine parent block copolymers composed of polystyrene and poly(2-vinylpyridine) having almost the same molecular weight but with different polystyrene volume fraction, φs, covering 0.1-0.9, were prepared. Successively they were blended variously to produce samples with various composition distributions but with constant average composition; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
136
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(151 citation statements)
references
References 19 publications
13
136
1
Order By: Relevance
“…A flurry of theoretical [25][26][27][28][29][30][31][32][33][34] and a͒ Authors to whom correspondence should be addressed: Electronic addresses: hillmyer@umn.edu and bates@cems.umn.edu. experimental 11,27,[35][36][37][38][39][40][41][42][43] studies of polydispersity effects in AB block copolymers followed Bendejacq et al's report. This topic recently has been reviewed, 44 and only a brief summary is provided below.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…A flurry of theoretical [25][26][27][28][29][30][31][32][33][34] and a͒ Authors to whom correspondence should be addressed: Electronic addresses: hillmyer@umn.edu and bates@cems.umn.edu. experimental 11,27,[35][36][37][38][39][40][41][42][43] studies of polydispersity effects in AB block copolymers followed Bendejacq et al's report. This topic recently has been reviewed, 44 and only a brief summary is provided below.…”
Section: Introductionmentioning
confidence: 91%
“…The reduction in elastic free energy is also accompanied by an increase in the height of end-grafted polymer brushes 17 and an increase in the domain period in the melt. [27][28][29]31,33,[35][36][37]43 Furthermore, the distribution of chain lengths present in polydisperse materials may stabilize additional ordered mesostructures. Listak et al 42 recently reported that polydispersity stabilized a hexagonally perforated lamellar mesostructure in poly͑styrene-b-methyl acrylate͒ diblock copolymers; this structure is considered metastable in nearly monodisperse materials.…”
Section: Introductionmentioning
confidence: 99%
“…Although long time the idea was set that ordered microphases in block copolymers can be achieved only by a narrow dispersity, [68] some studies have demonstrated their self-assembly into well-ordered structures even presenting a broader molecular weight distribution (MWD). [69][70][71][72][73] Our starting materials for the blends exhibit, with values of 1.16 and 1.19 for neat SIM and ISM, by themselves relatively broad MWDs and as both terpolymers have unequal molecular weights the combination in a blend provides both a polydispersity in molecular weight and composition. The repulsive segmental interactions between the copolymer blocks is the driving force for microphase separation and leads them to stretch in order to adopt a minimum of interfacial contact area.…”
Section: Resultsmentioning
confidence: 95%
“…The previous morphological observation for polydisperse block copolymers in composition and molecular weight clarified that lamellar domain spacing increases linearly with increasing the polydispersity in molecular weight or composition. [25][26][27] However, these results suggested only speculation on spatial distribution of the component block chains in microdomains. Thus, the segmental distribution of the component chains in block copolymer blends was directly examined by neutron reflectometry.…”
Section: Localization Of Component Chains In a Block Copolymer Blend mentioning
confidence: 88%
“…The evaluated segmental distribution in the block copolymer blend supported the previous morphological observations well. [25][26][27] Interdiffusion Behavior of a Cyclic Polystyrene Compared with a Linear Homologue A cyclic polymer has attracted much attention from the aspects of polymer physics due to its unique feature in molecular architecture with no chain ends. The existence of chain ends is essential for polymer dynamics such as diffusion and relaxation of a linear polymer chain in melt in the context of reptation theories.…”
Section: Localization Of Component Chains In a Block Copolymer Blend mentioning
confidence: 99%